Research progress in structure of sepiolite and its application in flame retardant polymer materials - MENG Jia-feng; MA Yuan; XIN Zhen-xiang; XIA Lin (Hecheng xiangjiao gongye, 2022)
In this paper, the basic structure of sepiolite was briefly introduced and its application in the flame-retardant field of common polymer composites was systemically reviewed with 21 references. The modification of sepiolite and its synergistic effect with other flame-retardants in the polymer compo-sites were emphatically discussed, and its application was looked forward.